PENGARUH PROLANIS DAN KEPATUHAN MINUM OBAT TERHADAP TEKANAN DARAH PASIEN HIPERTENSI DI PUSKESMAS GAMPING 1 - Niken Larasati; Nadia Husna (MEDIA ILMU KESEHATAN, 2019)
Background: Hypertension is one of the main risk factors for heart problems that require high medical costs. Prolanis is a health service system and proactive approach that is implemented in an integrated manner involving participants, health facilities, and BPJS Health in order to maintain health for participants. Objective: This study aims to determine the effect of implementing the Prolanis and medication adherence to blood pressure control in hypertension patients in Puskesmas Gamping 1. Methods: This research is non-experimental research and is observational analytic. Data collection was carried out retrospectively in June-September 2018. The data obtained were then analyzed by chi-square method. Results: The results obtained in this study were that there was no significant relationship between educational consultation with patient's blood pressure (Asymp. Sig. 0.111), and home visit with patient's blood pressure (Asymp. Sig 0.007). Furthemore there was a significant relationship between gateway reminder with patient's blood pressure (Asymp. Sig 0.002), and medication adherence with patient's blood pressure (Asymp. Sig 0,000). Conclusion: Success in controlling blood pressure in hypertensive patients is the result of cooperation between patients and medical and health care workers. Compliance and good understanding in carrying out therapy can affect blood pressure and gradually prevent complications.